The Impact of Digital Marketing, Product Quality, and Service Quality on Customer Satisfaction through Purchase Decision as Interacting Variables (Case Study of User Accurate Accounting Software In Jabodetabek Area) - Kumba Digdowiseiso; Yulia Kartika Sari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to examine the impact of digital marketing, product quality, and service quality on customer satisfaction via purchasing decisions as an intervening variable. The research sample consisted of 168 users of accurate accounting software in the JABODETABEK area. Questionnaires were used to collect data, and STATA 16.0 was used to analyze the data. According to the findings of this study, digital marketing, product quality, and service quality have a positive and significant impact on purchasing decisions. Customer satisfaction is positively influenced by digital marketing, product quality, and service quality. Purchase decisions have a positive and significant impact on customer satisfaction. Digital marketing has a positive and significant impact on customer satisfaction through purchasing decisions. Product quality has a positive and significant impact on customer satisfaction through purchasing decisions. Through purchasing decisions, service quality has a positive and significant impact on customer satisfaction.